Considerations and future perspectives for the vibrational spectroscopic analysis of forensic cosmetic evidence - Bruce, K.A.; Arnold, D.C.; Sauzier, Georgina; Lewis, Simon (John Wiley & Sons, Ltd, 2024)
Cosmetics such as makeup or other personal products are widely used and easily transferred upon physical contact. As such, they may be used as trace evidence to link people to each other or to places in criminal investigations. To maximize their probative value, it is important to understand the variability among representative market products and the way in which they transfer to, or persist on various surfaces. Additionally, it is required that analysis techniques be non-destructive, readily available and relatively inexpensive. Raman spectroscopy and attenuated total reflectance--Fourier transform infrared (ATR-FTIR) are powerful tools for probing the chemistry of trace cosmetics. As well as fitting the criteria above, they offer the capability of studying a wide range of sample types with minimal prior preparation. The complementary information derived from these techniques can help analysts to understand and visualize spectral variability, potentially enabling discrimination between samples. However, the move from academic research toward forensic casework is not without challenges. In this article, we provide a focused exploration of the current state-of-the-art in forensic cosmetic research; providing context for how we may begin to address these challenges to more effectively exploit cosmetic traces for criminal investigation. This article is categorized under: Forensic Chemistry and Trace Evidence > Emerging Technologies and Methods Forensic Chemistry and Trace Evidence > Trace Evidence